Enhancing maize yield in Ethiopia a meta-analysis - Tefera Merga; Weifang Zhang; Zhao Shuaixiang; Duan Zhiping (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Accurate nitrogen (N) fertilization and optimum plant density increase crop yields. In this study, I report the effects of N fertilization rate and plant density on maize yield in a meta-analysis, by using observations from 15 studies conducted in Ethiopia since the 2000s for possible refinement of N fertilizer and plant density recommendations. I assessed the response of maize to different N rates ha−1 compared to the control using the yield response approach. Application of N fertilizer significantly increased maize yields by 31.5% - 65.9% compared to control. plant density increased maize yields by 42% - 72.4% compared to the control. The interaction effect of the N rate increased maize yields by 27.6% - 95.9%, with Plant density, 58.7% - 152% on loam soil, compared to control yield. The interaction effect of Plant density with soil type increased maize yields by 47% - 108% on loam soil.  In conclusion, the grain yield of maize increased with increasing N rate and plant density up to the optimum. Therefore, it's possible to recommend using a high N rate with both low and medium plant density (< 45,000 plants ha-1) and (45,000 to 65,000plants ha-1) to harvest high grain yield.